Late Mesozoic marine Antarctic fi shes: future perspectives based on the newly collections recovered in the Ameghino and Lopez de Bertodano Formations - Gouiric Cavalli, Soledad (2017)
Nowadays, notothenioids are the teleostean group that dominates marine Antarctic waters.However, during the Mesozoic a diverse ichthyofauna inhabited the sea that surrounded Antarctic. Wepresent the preliminary results of the last two Argentinian Antarctic i eld expedition to the LateJurassic of Antactic Peninsula (Longing Gape) and Cretaceous-Paleogene of Seymour (=Marambio)Island. The i sh material recovered is extremely abundant and their further detailed study may providesignii cant clues into the taxonomy and paleobiogeography of the mesozoic antactic ichthyofaunas.